Analysis of urban farmers’ markets as a tourism product in Malaysia - Saili, Abdul Rahman (Curtin University, 2011)
Farmers‟ markets are an exciting and important form of free enterprise. They have a strong potential to support sustainable development due to the myriad of economic and social benefits they could bring to a society. Farmers‟ markets have been in existence in Malaysia for several decades, both in rural and urban areas. The role of farmers‟ markets in urban areas in Malaysia is important because they are a major source of fresh food for urban residents. They also offer an alternative to supermarkets and are a good source of a variety of products from fresh produce such as fruit and vegetables, fish and meat; processed food, cottage products, forest and jungle produce, indigenous products and other specialty products. Like most farmers‟ markets in other countries, farmers‟ markets in Malaysia have a folksy image, a characteristic that can be utilised to turn urban farmers‟ markets into a tourism product.Farmers‟ markets, so far, have not been seriously considered as a tourism product in Malaysia, yet, they have many benefits and advantages for consumers, producers and urban communities in terms of urban development and urban tourism. Malaysian urban farmers‟ markets are unique, with each of the markets having their own specialities. This character highlights the potential importance of urban farmers‟ markets as a tourist attraction. Urban farmers‟ markets also enjoy the privilege of being located in or near the city centre which traditionally is easily accessible to customers. If urban farmers‟ markets can be recommended as a component of urban tourism, it will not only benefit the local authority but may create a „chain reaction‟ which will then generate more benefits and opportunities for other stakeholders. Linking farmers‟ markets to tourism is also in line with the economic goals of most of the states in Malaysia, which are promoting themselves as tourist destinations. To date however, no study has yet been conducted into the possibility of linking urban farmers‟ markets to tourism in Malaysia. This study was therefore conceptualised.The key objective of this research is to analyse the potential of urban farmers‟ markets as a tourism product in Malaysia. Specifically, the study aimed to: (i) examine the current state of urban farmers‟ markets in Malaysia, (ii) examine the vendors‟ and tourists‟ levels of satisfaction with urban farmers‟ markets, (iii) explore the potential of urban farmers‟ markets as a tourism product, (iv) determine tourists‟ preferences and expectations of urban farmers‟ markets, and (v) recommend strategies to enhance urban farmers‟ markets as a tourism product in Malaysia.The case study approach was chosen as a research method to allow an in-depth examination of urban farmers‟ markets in Malaysia. The adoption of the case study technique fitted neatly with the triangulation techniques used in data gathering which, in turn, allowed the researcher to use multiple sources of data including interviews with key stakeholders such as the local authorities and tourism authorities, surveys with vendors and tourists, and use of secondary data such as reports and relevant documentation. The researcher‟s observations also helped add to the richness of the data.Four urban farmers‟ markets, two located in east of Malaysia and another two located in west of Malaysia, were selected for the study. Profiles of the farmers‟ markets were developed including the background of the markets, their history, regulations for market entry and support provided to the markets. The thesis drew on interview data, observations and documentations.There are two types of urban farmers‟ markets – non-structured (open-air) markets and structured markets. The non-structured markets operate at public car parks on weekends. The structured markets have a permanent building and operate on a daily basis. All markets accommodate more than 500 traders and are characterised by a festive bustle of activities with a wide variety of products offered to customers. All four farmers‟ markets have been in existence for over 20 years.The research also considered the vendors‟ and tourists‟ expectations with urban farmers‟ markets. The findings showed that vendors were generally satisfied with all market attributes except for the small vending space, toilet facilities, cleanliness and parking issues. Tourists also gave a satisfactory feedback on the market as a place for people to visit, with international tourists being more satisfied as compared to local tourists. The factors that attract tourists to visit urban farmers‟ markets include the wide variety of products on offer, easy access and the friendliness of people in the markets. However, the main drawbacks of the markets were the narrow (and sometimes hazardous) walkways and the low level of hygiene and cleanliness.There were several advantages of farmers‟ market that lend to their potential for being linked to tourism. For one, the markets have already been operating for more than 20 years and are well established. Secondly, and as mentioned earlier, there are numerous vendors and the demand, from potential vendors as well as current vendors, for more stalls demonstrate the strong interest from the „suppliers‟ of the products. Thirdly, vendors are keen to increase their tourist clientele. Moreover, the tourists‟ survey also revealed that majority of the tourists are aware of urban farmers‟ markets and are interested to visit the markets.Tourists‟ knowledge and awareness of farmers‟ markets mean that it is probable that they would consider visiting a farmers‟ market. In fact, the majority of the vendors in all the markets claimed that they have served tourists, although the number of visitors varied among the markets. Vendors would like to see more tourists purchase goods in farmers‟ markets. In all the case study markets, it was found that majority of tourists spent between RM51 to RM100 on their recent visit to an urban farmers‟ market. If farmers‟ markets are recognised as a genuine „tourism product‟ (and proper supporting mechanisms are put in place, such as promotions and media features in tourism magazines), then it is likely that the number of tourist visitors (and tourists‟ spend) in farmers‟ markets will increase in the future.The study also determined tourists‟ preferences and expectations of urban farmers‟ markets in Malaysia. A majority of the tourists expected to see local food, indigenous or specialty products, and culture demonstration, to visit or revisit an urban farmers‟ market. Factors that attract tourists to visit urban farmers‟ market include availability of indigenous products and the availability of local food. This is followed by culture demonstration and integration with festivals or celebrations.Policies suggested for urban farmers‟ markets focused on prominent issues highlighted by tourists, feedback from stakeholders and the literature in this area. The issue of cleanliness and hygiene was a main concern for tourists. Local authorities need to impose stricter regulations and vendors need to cooperate and make changes in their hygiene practices to keep the markets clean. At the same time, the management‟s rules and regulations should be based on the specific character of the market itself and should not detract from its distinctive character. This is to maintain the market‟s unique identity and differentiate it from other markets, thereby continuing to attract tourists. Similarly, as the variety of products sold in the market is considered one of the main attractions of urban farmers‟ markets, strategies to encourage creative and unique product offerings among vendors should be put in place so that more tourists will be attracted to visit and buy products from urban farmers‟ markets in Malaysia.